PEMBAHARUAAN HUKUM SISTEM PERADILAN PIDANA DALAM RUU KUHAP - Indra Ariska, Dudung (Universitas Wiralodra, 2019)
More than thirty years of the Penal Procedure Code are implemented in Indonesia. Law No. 8 of 1981 concerning the criminal procedural law in the beginning was seen as a